Overexpression of ZmIPT2 gene delays leaf senescence and improves grain yield in maize - Song, Yongfeng; Li, Chunxiang; Zhu, Yong; Guo, Pei; Wang, Qi; Zhang, Lin; Wang, Zhenhua; Di, Hong (Frontiers in Plant Science, 2022)
Cytokinins (CTKs) are a major phytohormone group that are significant in the promotion of cellular division, growth, and divergence. They also delay leaf senescence. In plant cytokinin (CTK) biosynthesis, isopentenyltransferase (IPT) regulates a rate-limiting step. Here, the full-length cDNA of ZmIPT2, which encodes 322 amino acids was isolated and was introduced into a maize inbred line by Agrobacterium-mediated transformation. In both controlled environments and field experiments, overexpression of the ZmIPT2 gene delayed leaf senescence in the transformed plants. Compared to the receptor line, the transgenic maize lines retained higher chlorophyll levels, photosynthetic rates, and cytokinin content for an extended period of time, and produced significantly higher grain yield by a margin of 17.71 % to 20.29 % under normal field planting conditions. Subsequently, a total of ten possible interactiongenes were analyzed by qRT-PCR, and the expression pattern of GRMZM2G022904 was consistent with ZmIPT2 expression. These results suggest that the productivity in maize can be improved by delaying leaf senescence utilizing the ZmIPT2 gene.